67. RESULTS OF THE PILOT IMPLEMENTATION OF THE MODEL OF COMBINATION IN TREATMENT OF SEVERE OSTEOPOROSIS IN-PATIENTS AT THONG NHAT HOSPITAL IN 2024 (Vietnam Journal of Community Medicine, 2024)
Background: Severe osteoporosis patients are hospitalized in many departments, have many complications, need to detect complications early, have timely treatment and treatment measures, so a unified process and coordination between many departments is needed.Objectives: Evaluate the results of the model of coordinated inpatient treatment of severe osteoporosis; Analyze the suitability and ability to maintain the model of coordinated treatment of severe osteoporosis at Thong Nhat Hospital in 2024Subjects and methods: Study of intervention in the treatment process of severe osteoporosis patients in 3 clinical departments for 3 months. Analyze and process data using SPSS 20.0 software.Results: The length of hospital stay before and after intervention 7-14 days increased (40.5%, 64.4%), over 14 days decreased (40.5% and 24.4%). The rates of performing the examination activities of "skin color of pressure area", "pain in the injured area", "mobility" before and after the intervention were (16.7%, 51.1%, p=0.001; 38.1%, 71.1%, p=0.002; 76.2%, 100%, p=0.001), respectively. The indications for infusion of anti-resorptive drugs, thrombosis prevention, and increased pressure stockings were statistically significant after the intervention (52.4%, 77.8%, p=0.013; 40.5%, 77.8%, p
Keywords: severe osteoporosis; specialized coordination